EXECUTIVE FUNCTIONS AND INTELLIGENCE IN TYPICALLY DEVELOPING CHILDREN - Buha, Nataša; Gligorović, Milica (Specijalna edukacija i rehabilitacija, 2016)
With regard to conceptual similarity between executive functions and intelligence, the aim of this research was to determine their correlation in typically developing children. The sample included 114 children of both sexes (59/51.8% of girls), between 8.7 and 10.8 years of age (M=9.80; SD=0.57). Dodrill's Stroop Test, Go/No-Go Task, Listening Span Task, Digit Span Backward, Odd-one-out span, Figure Span Backward, Wisconsin Card Sorting Test,  Twenty Questions Task and Tower of London were used for the assessment of executive functions. Intelligence was assessed by Raven’s Progressive Matrices. Pearson’s correlation and partial correlation coefficients were used in statistical analysis of the results. A low to moderate correlation was determined between intelligence and the variables of all applied executive functions tasks, both in verbal and non-verbal domain (p≤0.000-0.05). Inhibitory control, cognitive flexibility, and planning ability correlated with fluid intelligence in the range of r=0.20-0.30, while the correlation with working memory was in the range of r=0.40-0.50. The obtained results confirmed the assumption that intelligence and executive functions were different constructs regardless of their conceptual similarity. Key words: executive functions, intelligence, typical population